EFFECT OF MODIFICATION ON ELECTROSPUN NYLON 6,6 NANOFIBER MEMBRANE FOR PRETREATMENT OF PRODUCED WATER - ABD HALIM, NUR SYAKINAH (2019)
At the present time, massive amount of produced water (PW) waste has been generated and needs to be treated properly. Nanofiber membrane (NFM) has the potential to be applied as a filter due to its hugesurface area and high porosity. However, fouling issue and low mechanical strengthof NFM will reduce membrane performance over time. Therefore, membrane surface modification methods are applied to reduce fouling and promote crosslinking of nanofibers to improve the mechanical strength of membrane. In this study, two types of surface modification are applied to nylon 6,6 NFM produced by electrospinning; (1) blending of zeolitic imidazolate framework-8(ZIF-8) was used as an additive with loading of 0.2%, 0.4%, 0.6%, 0.8% and 1.0% and (2) solvent vapor treatment where the membrane was exposed to formic acid vapour for 5, 12, 24 and 48 hours.